Cienie przeszłości – refleksje z kilku wystaw - Nowicki, Paweł (Warstwy, 2017)
The article is based on personal memories. It describes three exhibitions which dealt with a reflection upon the inevitability of transience of all things. The exhibitions took place in the Museum in Gorlice (Dwory Karwacjanów i Gładyszów) and in the Polish-Slovakian Centre in Gorlice. The source of inspiration for this text were photographs by Bogdan Konopka and Robert Huk. The text mentions the local cemetery, once densely covered with trees, of which now very few are left. It deals with removing the spell and the romantic illusions, which comes along with modernity. This decline of the old atmospheric scenery shows the truth of our time. Perhaps against the intentions of those who have contributed to the felling of the trees, the bare cemetery shows the misery and tragedy of human existence.